(untitled) (Dentika: Dental Journal, 2010)
Disc displacement with reduction is one of the temporomandibular joint disorders which often occurred. Disc displacement can cause the changing of condyle position which can be evaluated by using radiograph. Cone Beam Computed Tomography (CBCT-3D) is a radiograph for viewing of the condyle with more accurate. The aim of this study was to determine the condyle position in disc displacement with reduction. Sample was 11 patients with disc displacement and 3 asymptomatic patients as control. A radiographic exposure was done with CBCT-3D and measurement of joint space in sagittal view was performed. Statistical analysis used T-test. The result of this study showed that there was significant difference (p<0,05) between disc displacement with reduction and asymptomatic patients. It can be concluded that there was different condyle position between disc displacement with reduction and asymptomatic patients. It means condyle position displacement caused sagittal joint space changed.